2017
DOI: 10.3389/fcimb.2017.00188
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Pandemic Vibrio parahaemolyticus O3:K6 and Its Serovariants: A Re-analysis of Strains Isolated from Multiple Studies

Abstract: In China, V. parahaemolyticus has been a leading cause of foodborne outbreaks and bacterial infectious diarrhea since the 1990s, and most infections have been associated with the pandemic V. parahaemolyticus O3:K6 and its serovariants. However, a comprehensive overview of the sero-prevalence and genetic diversity of the pandemic V. parahaemolyticus clone in China is lacking. To compensate for this deficiency, pandemic isolates in both clinical and environmental Chinese samples collected from multiple studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…The antibiotic tests showed different results from those reported in previous studies. The resistance of V. parahaemolyticus environmental isolates to AMP was fully confirmed and is consistent with findings of previous studies (Han et al, 2017;Jiang et al, 2019). However, the resistance of V. parahaemolyticus environmental isolates to quinolones and cephalosporins, especially to CAZ and CIP, which was confirmed by Lopatek et al (Lopatek et al, 2018), could not be established by this method.…”
Section: Antibiotic Resistance Of V Parahaemolyticussupporting
confidence: 88%
“…The antibiotic tests showed different results from those reported in previous studies. The resistance of V. parahaemolyticus environmental isolates to AMP was fully confirmed and is consistent with findings of previous studies (Han et al, 2017;Jiang et al, 2019). However, the resistance of V. parahaemolyticus environmental isolates to quinolones and cephalosporins, especially to CAZ and CIP, which was confirmed by Lopatek et al (Lopatek et al, 2018), could not be established by this method.…”
Section: Antibiotic Resistance Of V Parahaemolyticussupporting
confidence: 88%
“…From 1996 to 2007, up to 22 pandemic serovariants were identified around the world ( Nair et al, 2007 ). The latest report increased this number to 27 ( Han et al, 2017 ), suggesting that the pandemic isolates could easily adopt new serotypes to survive in new environments. Whole-genome sequence analysis of three pandemic isolates, including one with a different serotype (O4:K68) ( Chen et al, 2011 ), showed high similarity along the whole genome in this clonal complex except in the O- and K-antigen-encoding gene clusters, which contained 94% of the SNVs.…”
Section: Evolution Of the Pandemic Strainmentioning
confidence: 99%
“…In general, these analyses together with eBurst ( Feil et al, 2004 ) showed that most pandemic strain isolates cluster within a single clonal complex (CC3), with most showing the founder single sequence ST3 and multiple single and double locus variants (SLV and DSV). Recent MLST analysis of isolates from China showed 15 sequence types, revealing increasing genetic diversity among pandemic isolates, 10 of which fell within CC3 ( Han et al, 2017 ). The isolates also showed frequent recombination among the genes or loci included in the MLST.…”
Section: Evolution Of the Pandemic Strainmentioning
confidence: 99%
“…Therefore, the current assay presents a simple and pragmatic scheme for the rapid and accurate identification of V. parahaemolyticus serotypes, which is especially suited for real-time applications such as outbreak situations involving large number of samples be processed quickly in a short period of time. In developing this assay, we chose 11 V. parahaemolyticus serotypes that represented 90% of all serotypes isolated from human infections over a 10-year period (2007–2017) in Shenzhen, China; many of which are also commonly reported among infections domestically (Han et al, 2017) and worldwide (Velazquez-Roman et al, 2014; Han et al, 2016). Given its clinical relevance, the current assay could serve as an invaluable tool for clinical and public health laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the pandemic clone and its serovariants are known to represent 49 serotypes, which are widely distributed among 22 countries in Asia, Europe, America and Africa (Han et al, 2016). In China, up to 27 pandemic serovariants have been found amongst clinical samples, in which O3:K6, O4:K68, and O1:KUT predominated (Han et al, 2017). Hence, the serotyping of V. parahaemolyticus has played a pivotal role in significantly advancing our understanding of its epidemiology.…”
Section: Introductionmentioning
confidence: 99%